1978
DOI: 10.3382/ps.0571266
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antimicrobial Agents for the Extension of Poultry Shelf-Life

Abstract: Fifty three chemicals were evaluated for their antimicrobial activity around neutral pH against five predominant cultures isolated from spoiled poultry and three reference organisms. Eleven of these chemicals were found to be effective in the desired pH range of 6.5 to 7.5. Two of the eleven chemicals, iodoacetamide and chloroacetamide, were found to inhibit the growth of spoilage organisms at concentrations of 30 and 80 ppm respectively. Freshly processed broilers were immersed in solutions of these two chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The psychrophile counts on the glutaraldehyde and iodoacetamidetreated birds were slightly more than lo2 organisms/cm2 of skin. As observed by Islam et al (1978), for the control birds immersed in water, there was a slight decrease in the psychrophile count which may be attributed to the mechanical rinsing effect.…”
Section: Bacterial Countmentioning
confidence: 65%
See 3 more Smart Citations
“…The psychrophile counts on the glutaraldehyde and iodoacetamidetreated birds were slightly more than lo2 organisms/cm2 of skin. As observed by Islam et al (1978), for the control birds immersed in water, there was a slight decrease in the psychrophile count which may be attributed to the mechanical rinsing effect.…”
Section: Bacterial Countmentioning
confidence: 65%
“…Since several studies (Ayres et al 1950;Walker and Ayres 1956;Nagle et al 1960;Arafa and Chen 1975) indicated psychrophiles to be the most dominant organisms in spoiled poultry, total aerobic psychrophile counts of the birds were obtained during the storage period a t 5-day intervals. The procedures followed for swabbing, incubation and enumeration were the same as described by Islam (1978). Out of the 4 birds designated for bacterial count, 2 were swabbed on the right breast before and after dipping on day 0, and then on the left breast on day 5 and 10.…”
Section: Bacterial Countmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have evaluated the use of various chemicals in processing waters to reduce or eliminate salmonellae on processed poultry (Cunningham and Lawrence, 1977;Thomson et al, 1977;Islam et al, 1978;Lillard, 1979;Thiessen et al, 1984). Many of the chemicals studied have shown promise in reducing or eliminating certain microorganisms.…”
Section: Introductionmentioning
confidence: 99%